Pendampingan dalam Pengolahan Nastar dari Nanas bagi Masyarakat Dukuh Barak 1 - Annafii, Argya Muhammad; Saputra, Naufal Ahmad; Pangestu, Bangun Yoga; Ghofari, Alfiga; Ramadhani, Noviana; Nani, Sri Marfah; Ardiyan, Muhammad Rizky; Shabella, Nita; Fathurrahman, Amar Ghifari; Azhari, Miftahurrizqi Putri; Febriani, Erma (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Community Service Program (KKN) is a community service program that aims to develop local potential and improve community welfare. Regular KKN Group 105 of Muhammadiyah University of Yogyakarta for the 2024/2025 period was implemented in Dukuh Barak 1, Margoluwih Village, Seyegan District, Sleman Regency, with the theme "Developing Human Resource Potential to Improve Community Quality of Life", with a focus on optimizing the potential of pineapple farming as an alternative economic source. Initial observations showed that pineapple cultivation in Dukuh Barak 1 was still in its early stages and the utilization of pineapple agricultural products was not optimal. Therefore, the main KKN program focused on mentoring and training in processing pineapple into high-value economic products, one of which was making pineapple-based nastar cookies. This program aims to improve community understanding and skills related to processing nastar from pineapple. The implementation method used includes several stages, namely socialization, preparation, implementation, and monitoring and evaluation. The training was conducted using demonstration and hands-on practice methods, attended by 25 participants who were representatives of mothers from each RT in Dukuh Barak 1. This training aims to improve community skills in processing agricultural products into high-value products. The results of the activity showed that the cooking training received a positive response from the community with active participation and increased participant skills. This training produced pineapple-based nastar products that have the potential to be developed as superior village products. Evaluation of the activity was carried out by filling out a questionnaire to measure the effectiveness of the training. The evaluation of the activity showed that more than 85% of participants were very satisfied with the training provided. The evaluation results showed that this training had a positive impact in several main aspects, such as increasing participant understanding, skills, and performance. With these results, the training can be said to be successful in providing significant benefits, especially in improving participant skills and insights in related fields